Reactive thrombocytosis in pulmonary tuberculosis. Issue 6 (June 1987) - Baynes, R D; Bothwell, T H; Flax, H; McDonald, T P; Atkinson, P; Chetty, N; Bezwoda, W R; Mendelow, B V
Abstract : The incidence of reactive thrombocytosis in active pulmonary tuberculosis was studied in 122 patients. Thrombocytosis was common, platelet counts often exceeding 1 X 10(12)/1. A significant inverse correlation was noted between the mean platelet volume and the platelet count (r = -0.54, p less than 0.0001). Interval estimation suggested that this relation was non-linear. Further studies were done in a small group of six patients. Platelet survival was considerably shortened, the platelets aggregated excessively in vitro, serum concentrations of thrombopoiesis stimulating activity were raised, and serotonin uptake and release were within normal limits. The degree of thrombocytosis correlated significantly with the degree of inflammation measured by the erythrocyte sedimentation rate (r = 0.40, p less than 0.003) and serum C-reactive protein concentration (r = 0.35, p less than 0.008).